Defensible record keeping - Rayamajhi, P; Guragain, RPS (Journal of Institute of Medicine Nepal, 2007)
Background: This retrospective study was conducted by the department of ENT and Head & Neck Surgery, TU Teaching Hospital to evaluate the maintainance of records of the inpatients in TU Teaching Hospital. The rolling audit was performed to evaluate the implementation of the recommendations made. Material and Methods: Total of twenty files from each of the eight departments with the inpatient wards was reviewed retrospectively on January 2004. Similarly, other twenty files from each department were studied for the rolling audit on October 2006. The notes were reviewed for completeness and inclusion of the criteria as laid down in the protocol by the Royal College of Surgeon. Results: The admission notes were adequately filled in the department of Psychiatry. The progress notes were adequately filled in the department of Psychiatry and ENT-HNS. The investigation form filling was comparable in all the departments. The discharge summaries were complete and understandable in the department of Psychiatry followed by ENT-HNS. Significant improvement was seen in the department of Obstetrics and Gynecology during the rolling audit. Conclusion: The rolling audit can be done every 6 month to assess the maintainance of the records and the implementation of the recommendations. Key Words: Audit; Defensible record keeping; Royal College of Surgeons The full text of this paper is available at Journal of Institute of Medicine website